Shopping simulation: BTS army hyper-reality on the Tokopedia marketplace - Dwi Retnani Srinarwati (Faculty of Communications Science, Dr. Soetomo University, 2023)
This paper explores the phenomenon of hyperreality within the context of online shopping and fandom culture, focusing specifically on the vibrant and dedicated fanbase of the popular South Korean boy band BTS, known as the BTS Army. Drawing upon the virtual marketplace of Tokopedia as a case study, we investigate the unique and immersive shopping experiences created by the BTS Army as they engage with merchandise related to their favourite band. Qualitative content analysis with Baudrillard Theory perspectives is used to unravel the complexities of the BTS Army's consumer behaviour, purchasing patterns, and collective interactions within this simulated environment. The findings demonstrate that the Tokopedia marketplace is a hub for the BTS Army, where fans navigate a hyperreal shopping landscape infused with emotional connections, shared meanings, and transformative experiences. Through acquiring and displaying BTS-related merchandise, fans construct and reinforce their identities, cultivate a sense of belonging, and participate in a hyperreal world that blurs the boundaries between fandom and consumer culture. It provides insights for marketers, platform operators, and researchers into the dynamics of hyperreal fandom-driven markets, emphasising the significance of emotional engagement, community building, and immersive experiences for capturing the attention and loyalty of dedicated fan communities.